Distribution Level Aggregator Platform for DSO Support—Integration of Storage, Demand Response, and Renewables - Ali, Jibran; Massucco, Stefano; Silvestro, Federico (Frontiers in Energy Research, 2019)
Modern era is full of renewable energy resources, particularly wind and solar that are installed at both Low and Medium voltage nodes of the distribution system. With the diffusion of new resources in the distribution grid, a new challenge for the system operators is to cope up with the introduced changes in the distribution network. These changes can be on voltage levels, magnitudes and direction of current, and changes in power factor. The reduced visibility of these additives to operators require provision of ancillary services to ensure power system reliability and stability. In order to give flexibility to operator, and in particular DSO for distribution grid, the paper suggests the use of distribution level aggregators to serve as sub-DSO (JDSO). These aggregators utilize the three main components: Electrical energy storage system, customers demand response, and the renewable resources (PV and wind). These aggregators utilize a platform where all these actors can participate. DSO-JDSOs interaction is possible through the platform, and the local problems at distribution can be resolved before it goes to TSO. Paper presents and simulates the platform, develop test cases, and validate the model.